Potential Medication Error in Patient Prescriptions at Class II Hospital 14.05.01 Pelamonia Makassar 2025 (International Forum of Researchers and Lecturers, 2025)
Medication errors (MEs) are preventable events that may cause or lead to inappropriate medication use or patient harm while the medication is in the control of healthcare professionals, patients, or consumers. These errors can occur at various stages of the medication process and are a significant concern for patient safety. The primary phases of ME include prescribing, transcribing, and dispensing. Understanding the distribution and frequency of these errors is essential for improving the quality of healthcare services. The objective of this study was to determine the potential for medication errors in outpatient prescriptions at Class II Hospital 14.05.01 Pelamonia Makassar. A quantitative research method was applied, involving the analysis of 100 prescriptions collected from various clinics, including neurology, pediatrics, pulmonology, urology, internal medicine, ENT, oncology surgery, mental health, ophthalmology, dermatology, cardiology, and dental services. Data were analyzed to identify potential errors in each phase of the prescription process. The results revealed that the prescribing phase had the highest potential for MEs, accounting for 20.18% of the total errors identified. Errors detected in the transcribing phase constituted 2.72%, while errors in the dispensing phase accounted for 2.45%. These findings suggest that the prescribing stage represents the most critical point of vulnerability in the medication use process, where targeted interventions and enhanced monitoring may significantly reduce the risk of errors. In conclusion, the pharmacy installation at Class II Hospital 14.05.01 Pelamonia Makassar must prioritize strategies to minimize prescribing errors, such as improving physician training, implementing prescription review systems, and enhancing interprofessional communication. Reducing MEs will contribute to better patient outcomes and improved overall healthcare quality.